Materials for hydrogen-based energy storage – past, recent progress and future outlook - Hirscher, M.; Yartys, V.A.; Baricco, M.; Bellosta von Colbe, J.; Blanchard, D.; Bowman, R.C.; Broom, D.P.; Buckley, Craig; Chang, F.; Chen, P.; Cho, Y.W.; Crivello, J.C.; et al. (ELSEVIER SCIENCE SA, 2020)
© 2020 The Authors